PENERAPAN VIDEO NEU IN BERLIN-DIE ERSTE BEGEGNUNG UNTUK KETERAMPILAN MENYIMAK BAHASA JERMAN SISWA KELAS X SMA NEGERI 12 SURABAYA - HASNA R, ARISTA (LATERNE, 2017)
Language skills has four competens, there are listening comprehension, speaking, reading and writing. Listening comprehensions has an important contribution to other skills. But the fact is listening comprehension is difficult for the students, so the teacher needs interesting teaching materials namely audio-video (audiovisual). The video Neu in Berlin-Die erste Begegnung from the website www.lingorilla.com is an option. The problem in this investigation is how use of the video Neu in Berlin-Die erste Begegnung for Listening Comprehension in German Lessons to the Class X students SMAN 12 Surabaya. The goal of this study is to describe the use of the video Neu In Berlin-Die erste Begegnung for Listening Comprehension in German Lesson Class X SMAN 12 Surabaya. This study uses qualitative examination method. The data of this study are observation data. The results showed that the video Neu in Berlin-Die erste Begegnung gives the pupils the opportunity to actively participate in teaching and learning activities, because the teachers implementation the application of the video " Neu in Berlin-Die erste Begegnung" And manage with smile, zeal and relaxed. Teachers have control over the media and material presents students so that students can easily understand the material, more enthusiastic and more active in learning. The video Neu in Berlin-Die erste Begegnung is expected to add variations of educational media in the form of video for teachers to be more creative and innovative in order to improve the motivation to learn the German language and to have a positive influence on the learning results to have. Keyword : The Video Neu in Berlin-Die Erste Begegnung, Listening Comprehension, Personalpronomen.